The Shadow - Patterson, James, 1947-; Sitts, Brian (New York ; Boston : Grand Central Publishing, 2021)
Awakening in a world both unknown and disturbingly familiar, Lamont Cranston, aka the Shadow, must once again go up against his fiercest enemy, Shiwan Khan, and prove that he is not only a super crime-fighter, but an icon.
Only two people know that 1930s society man Lamont Cranston has a secret identity as the Shadow, a crusader for justice. One is his greatest love, Margo Lane; the other his fiercest enemy, Shiwan Khan. When Khan ambushes the couple, Lamond awakens a century and a half later-- in a world both unknown and disturbingly familiar. He meets Maddy Gomes, a teenager with her own secrets. And Khan's power continues to be felt over the city and its people. Only the Shadow has a chance of succeeding in stopping Khan-- before more innocent lives are lost. -- adapted from jacket
"Crime has a new enemy" -- Jacket.
"James Patterson's explosive reimagining of the iconic detective who has thrilled readers across generations" -- Front jacket flap
Includes James Patterson's recommended reads.
Keywords: Shadow -- (Fictitious character) -- Fiction; Shadow -- (Fictitious character); Superheroes -- Fiction; Teenage girls -- Fiction; Time travel -- Fiction; Superheroes -- Fiction; FICTION / Thrillers / Suspense; FICTION / Thrillers / Crime; FICTION / Superheroes (see also COMICS & GRAPHIC NOVELS / Superheroes).; Criminals; Heroes; Superheroes; Teenage girls; Time travel; Time travel -- Fiction; New York (N.Y.) -- Fiction; New York (State) -- New York; Superhero fiction; Suspense fiction; Fiction; Science fiction; Superhero fiction; Thrillers (Fiction); Time-travel fiction; Thrillers (Fiction); Thrillers (Fiction); Time-travel fiction; Superhero fiction; Novels